Thinking Profile of Mathematics Teachers in Solving HOTS Problems - Darmadi, Darmadi; Sanusi, Sanusi; Budiyono, Budiyono; Soleh, Dwi Rohman; Rifai, Muhammad (Journal of Education Method and Learning Strategy, 2023)
HOTS questions are given by teachers in learning with the hope that students will be able to think at a higher level. The aim of this research is to obtain a profile of mathematics teachers' thinking in solving HOTS problems. The research method used is a qualitative approach. The research subjects were SMA/SMK/MA teachers who worked and lived in Madiun, Magetan, Ngawi, and Ponorogo. Data collection uses tests and in-depth interviews. Source and time triangulation is used to obtain valid data. Categorization, reduction, and coding are used for data analysis so that conclusions can be drawn. Mathematics teachers solve HOTS problems by understanding, planning, implementing, and checking again. When understanding, mathematics teachers take the information contained in the problem given and bring it into mathematical form. At the understanding stage, teachers can identify the suitability of problems with their knowledge, such as linear programming problems. This is done by considering possible answers according to the information available on the problem. When implementing, according to the choices decided, the teacher carries out the plan. Implementation of the plan is the teacher's answer to solving the given HOTS problem. When rechecking, in general, perhaps because of the hassle, some mathematics teachers do not recheck answers. Only after there has been a discussion do most math teachers check their answers again. At this stage, it is possible for the teacher to find doubts and decide on confidence in the answer.